Courting Failure - LoPucki, Lynn (University of Michigan Press, 2023)
LoPucki's provocative critique of Chapter 11 is required reading for everyone who cares about bankruptcy reform. This empirical account of large Chapter 11 cases will trigger intense debate both inside the academy and on the floor of Congress. Confronting LoPucki's controversial thesis-that competition between bankruptcy judges is corrupting them-is the most pressing challenge now facing any defender of the status quo."" -Douglas Baird, University of Chicago Law School